2000
DOI: 10.1094/mpmi.2000.13.7.763
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Eight Chitinase Genes in Medicago truncatula Roots During Mycorrhiza Formation, Nodulation, and Pathogen Infection

Abstract: Expression of eight different chitinase genes, representing members of five chitinase classes, was studied in Medicago truncatula roots during formation of arbuscular mycorrhiza with Glomus intraradices, nodulation with Rhizobium meliloti, and pathogen attack by Phytophthora megasperma f. sp. medicaginis, Fusarium solani f. sp. phaseoli (compatible interactions with root rot symptoms), Ascochyta pisi (compatible, symptomless), and F. solani f. sp. pisi (incompatible, nonhost interaction). In the compatible pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 76 publications
6
138
0
3
Order By: Relevance
“…Although chitinases can be induced in pathogenic interactions (Salzer et al 2000), specific class III chitinases have been found to be up-regulated in arbuscular mycorrhizal (AM) Medicago truncatula roots, but not in interactions with pathogens (Salzer et al 2000). Predominant expression of these chitinases was in the arbuscule-containing cells (Bonanomi et al 2001;Hogekamp et al 2011), where they may play a role in suppressing plant defence by the reduction of chitin-like elicitors during the formation of functional symbiotic interfaces (Salzer et al 2000). A similar role may be envisaged in S. vomeracea mycorrhizal protocorms, but further studies are required to investigate regulation of SvChit3 by other biotic and abiotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Although chitinases can be induced in pathogenic interactions (Salzer et al 2000), specific class III chitinases have been found to be up-regulated in arbuscular mycorrhizal (AM) Medicago truncatula roots, but not in interactions with pathogens (Salzer et al 2000). Predominant expression of these chitinases was in the arbuscule-containing cells (Bonanomi et al 2001;Hogekamp et al 2011), where they may play a role in suppressing plant defence by the reduction of chitin-like elicitors during the formation of functional symbiotic interfaces (Salzer et al 2000). A similar role may be envisaged in S. vomeracea mycorrhizal protocorms, but further studies are required to investigate regulation of SvChit3 by other biotic and abiotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Staehelin et al, 1992;Vasse et al, 1993;Mithö fer et al, 1996;Goormachtig et al, 1998;Salzer et al, 2000). The demonstration that NopL is a repressor of plant defense reactions suggests that invading rhizobia can manipulate metabolic pathways of their hosts using mechanisms that are common to pathogens.…”
Section: Table I Plant Growth and Nodule Formation Of L Japonicus Pmentioning
confidence: 99%
“…Transcripts of the class IV chitinase gene, Mtchit 4, continuously accumulated in the interaction of M. truncatula Jemalong A17 with S. meliloti 1021. In our previous work (Salzer et al 2000), however, we were not able to identify a chitinase gene that is specifically induced during interactions with S. meliloti. In order to learn more about chitinase gene expression during nodule formation and about the effects of rhizobial signal molecules, we extended our studies on the M. truncatula ecotype R108-1.…”
Section: Introductionmentioning
confidence: 67%
“…Culture and inoculation with the AM fungus Glomus intraradices was performed as previously described (Salzer et al 2000) with about 400 spores, which had been isolated from Daucus carota/Glomus intraradices in vitro cultures (Be´card and Fortin 1988). In control experiments, an equivalent amount of water was added.…”
Section: Treatments and Culture Of Plants Bacteria And Fungimentioning
confidence: 99%
See 1 more Smart Citation